Pemanfaatan Digital Marketing Pada Penjualan Produk UMKM - ., Marwan; Ismail; Arifin, Fikri (LPPM Universitas Potensi Utama, 2022)
UMKM Bunda Rasya is a home industry that is engaged in the production process in managing raw materials for bananas and sweet potatoes into a product of banana chips and sweet potato chips which will be marketed as snacks for the Indonesian people. Until now, Bunda Rasya UMKM do not have a marketing system, so there is no promotion of the products they produce. The order for chips has not experienced a significant increase so far, and even experienced a slight decrease in sales due to decreased production per day. Based on the observations of researchers in an effort to restore the current condition of UMKM sales due to the impact of the Covid-19 pandemic which has not yet been completed, that one of the factors that influence the lack of sales orders is the absence of marketing. So that it is difficult for companies to get new consumers, given the importance of marketing in a business, a strategic plan is needed to determine the right marketing strategies for Bunda Rasya UMKM, namely digital marketing. The steps for using digital marketing are as follows: 1. Determine a personal buyer. 2. Identify the needs of the target market. 3. Prepare a marketing plan. 4. Take advantage of various digital marketing media (google my business, instagram, facebook, whatsapp business, website, etc.). 5. Apply an attractive copy writing strategy. 6. Use marketing tools for business. 7. Understand digital marketing metrics and evaluations. After making direct observations during the activity, this activity gave results, namely providing input to business management in making product marketing strategies. business management becomes more mastered and understands the importance of marketing strategies in the business world, especially UMKM in the field of digital marketing